A differential evolution proposal for estimating the maximum power delivered by CPV modules under real outdoor conditions. Issue 13 (1st August 2015) - García-Domingo, B.; Carmona, C.J.; Rivera-Rivas, A.J.; del Jesus, M.J.; Aguilera, J.
Highlights Multivariable model to calculate the maximum power given by concentrating modules. Spectrum additional indexes in the equation proposed by the standard methodology. Calculation of regression coefficients by a differential evolution algorithm. Applicability to the forecasting of the energy produced by big power plants.